0197 Associations between Sleep and Emotion Regulation in Isolated, Confined, and Extreme Environments. (27th April 2018) - Bower, J L; Laughlin, M; Simpson, R J; Connaboy, C; Alfano, C A
Abstract: Introduction: Understanding interactions between sleep and emotion in isolated, confined, extreme environments (ICEs) is relevant to multiple populations (e.g., military personnel, off-shore workers, astronauts). Little is known about risk and resilience factors affecting sleep in these environments; however conditions (e.g., loss of natural light, communication delays) are conducive to sleep, circadian, and emotional disturbances. This study assesses sleep, neurobehavioral and emotion regulation factors in the Human Exploration Research Analog (HERA), a highly controlled, 3-story analog, simulating human exploration into space. Methods: Sixteen participants (9 male) aged 29–52 ( M =36.38, SD =7.11) completed a 30-day mission in HERA. Actigraphy data was collected continuously, including 11 days pre-mission. Subjective sleep complaints (Sleep Self-Assessment Scale; pre-mission, mission day 7 (D7), and D14), neurobehavioral symptoms (Neurobehavioral Checklist [NBCL]; pre-mission, D4, D11, D18), and pre-mission emotion regulation (including Anxiety Sensitivity Index and Difficulties in Emotion Regulation Scale) were also measured. Analyses included data from D0-D24, after which a sleep manipulation occurred. Results: Pre-mission, positive adaptation was negatively associated with subjective sleep complaints ( r t = -.47, p =.02). Variability in total sleep time (TST) was negatively associated with emotion regulation difficulties ( r t = -.494, p =.02) and poor self-regulation ( r t =-.55, p =.02), whilst individuals with higher anxiety sensitivity showed increased sleep percentage ( r t =.45, p =.04) and decreased wake after sleep onset ( r t = -.43, p =.05). During mission, TST increased, with a significant overall change from pre-mission to D18 ( F (2.26, 27.16)=8.91, p =.001, η 2 partial =.45). Early in the mission (D1-D4), subjective sleep complaints were positively associated with poor self-regulation ( r t= .56, p=.005). During D1-D4, sleep onset latency (SOL) was negatively associated with anxious apprehension ( r t =-.46, p =.02) and marginally associated with poor self-regulation ( r t =-.31, p =.11). In subsequent mission days (D4-D11 and D11-18) the negative association between poor self-regulation and SOL was maintained ( r t =-.47, p =.02 and r t =-.47, p =.01 respectively). Conclusion: Associations identified between emotional functioning and sleep provide potential indicators of individual risk and resilience patterns within ICEs. Such findings await replication in larger samples and across different environmental conditions. Support (If Any): National Aeronautics and Space Administration grant: NNX15AC13G awarded to C.A. Alfano and R.J. Simpson.